Exploring the Reading Practices of Undergraduate Students. Issue 3 (3rd July 2018) - St Clair-Thompson, Helen; Graham, Alison; Marsham, Sara
ABSTRACT: Research in higher education has revealed that only a small proportion of students complete assigned reading during semester. The current studies examined students' reading practices, and sought to explore potential factors underlying these practices. Three studies were conducted. Study 1 utilised a questionnaire to examine how long students spend reading academic material. Students reported spending an average of 14.1 hours per week reading a range of sources, including textbooks and journal articles for both guided and independent reading. The number of hours spent reading was lower than university expectations. Study 2 involved conducting focus groups to explore potential factors underlying students' reading practices. Six main themes emerged in the data; Expectations, Perceived benefits, Course structure, Lack of time, Practicalities, and Confidence. Study 3 further examined students' perceptions of a lack of time and a lack of confidence with reading using a diary exercise and a further questionnaire. The diary exercise revealed that students spent an average of 6.5 hours per day engaged in academic activities. In addition, students were generally confident with reading, although more so with reading textbooks than journal articles. The findings are discussed in terms of implications for staff teaching in higher education.